Jesus the Christ and the Judgment of God in New Testament Theology - Chandra Gunawan (Cipanas Theological Seminary, 2022)
Scholars disagree if there is a New Testament theology. While many scholars claim that there are diversities within NT, some argue that eschatology, especially the teaching about judgment probably can become a theological theme connecting the NT. This article will examine that proposal. The research question is how to understand the role of the teaching of Judgment in the New Testament theology. This article will employ historical-critical exegesis to investigate the teaching of judgment in the NT texts and will argue that, although the teaching of judgment is common in the NT, it is not a core of NT theology; the teaching about Jesus is the central theme of the NT theology.